Depression and Five Year Survival Following Acute Myocardial Infarction - Carney, Robert M. (2008)
BACKGROUND: Depression has been shown to be a risk factor for mortality during the 12 months following an acute myocardial infarction (MI), but few studies have examined whether it is associated with increased risk over longer periods. Most of the existing studies utilized depression questionnaires rather than diagnostic interviews, the gold standard for clinical depression diagnosis. The purpose of this study was to determine whether interviewed-diagnosed clinical depression affects survival for at least 5 years after an acute MI. METHODS: Vital status was determined for 163 patients with major depression, 195 with minor depression or dysthymia, and 408 nondepressed patients, during a median follow-up period of 58 months after an acute MI. Survival analysis was used to model time from the index MI to death. RESULTS: There were 106 deaths during the follow-up. After adjusting for other risk factors for mortality, patients with either major or minor depression (HR = 1.76; 95% CI: 1.19 to 2.60), major depression alone (HR = 1.87; 95% CI: 1.17 to 2.98), or minor depression alone (HR = 1.67; 95% CI: 1.06 to 2.64) were at higher risk for all-cause mortality compared to the nondepressed patients. CONCLUSIONS: Depression is an independent risk factor for death 5 years after an acute MI. Even minor depression is associated with an increased risk. Although it is not known whether treating depression can improve survival, patients with depression should be recognized as being at increased risk long after their acute MI.